An Empirical Investigation of the Prevalence of Osteoarthritis in South West Nigeria: A Population-Based Study - Aderonke, Kayode Anthonia; Oluwatobi, Akande Noah; Jabaru, Saheed O; Tinuke, Oladele O (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Today, Osteoarthritis remains the most prevalent chronic joint disease and a potentially incapacitating joint illness. It is an enduring health problem which cannot be cure though it can be managed. Osteoarthritis remains a serious public health problem because its burden is high, people who live with it have a greater risk of developing anxiety / or depression and if it is not properly managed, it can bring about disability as well as impairing quality of life. This paper presents a statistical correlation between the reported risk factors of Osteoarthritis and its prevalence in Nigeria. Statistical tests were performed to investigate if there is enough evidence for inferring that the risk factors for Osteoarthritis are true for the whole of Nigerian population